In-house media accountability instruments: Spanish journalists' and citizens' perceptions - Ramon, Xavier (2020)
In a context characterized by structural transformations and the credibility crisis of journalism, media accountability is of outmost importance. Focusing on the Spanish context, this article examines journalists’ and citizens’ perceptions of in-house accountability instruments. To do so, an online survey was administered to Spanish journalists, six citizen focus groups were established and 19 in-depth interviews were conducted with experts and representatives from professional associations. The results reveal that journalists’ evaluation of media accountability instruments is modest. From the citizens’ perspective, the lack of visibility and relative distrust toward these instruments are highlighted. With the goal of stimulating the debate and decision-making, an open access platform has been built to evaluate if media organizations have developed these fundamental instruments to promote transparency, self-regulation and participation.